Intervención fisioterapéutica en paciente femenino de 64 años con tendinopatía rotuliana en miembro inferior izquierdo. - Gutiérrez Bustamante, Joshua Alexander (2025)
A 64-year-old female patient, who reported having practiced athletics in her youth, went for a check-up with a rheumatologist who referred her for physiotherapeutic treatment after an MRI showed wear and tear in the patellar tendon of the left lower limb. The patient presented symptoms of intense pain and swelling in the affected area, which prevented her from performing activities such as going up and down stairs, as well as discomfort when walking. In the initial evaluation, there was pain on palpation of the patellar tendon as well as functional limitation and difficulty in performing daily activities. His diagnosis was degenerative patellar tendinopathy, which is related to his sports history and tissue aging. Her treatment included eccentric muscle strengthening exercises, specific stretching for the lower extremity, proprioceptive exercises and joint mobility techniques which are based on a comprehensive physiotherapy plan. In addition, electrotherapy, magnetotherapy, therapeutic ultrasound and cryotherapy were used in order to reduce pain and inflammation, promoting tendon regeneration. After a period of time within the physiotherapeutic treatment plan, the patient reported a significant decrease in pain, an improvement in functional stability and the ability to perform daily activities, including walking and using stairs with less discomfort. She was also educated about her condition and provided strategies to avoid tendon overload, favoring an adequate adaptation to her lifestyle. The results obtained thanks to the physiotherapeutic approach reinforce the efficacy of personalized treatment in the management of patellar tendinopathy.